2016
DOI: 10.9778/cmajo.20160080
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of MCR-1-mediated colistin resistance among Escherichia coli clinical isolates obtained from patients in Canadian hospitals (CANWARD 2008-2015)

Abstract: Background: Colistin is often used as an antimicrobial of last resort for the treatment of infections caused by multidrug-resistant gram-negative bacilli. In 2015, plasmid-mediated colistin resistance in Escherichia coli due to MCR-1 was described. The purpose of this study was to evaluate the frequency of colistin resistance among E. coli clinical isolates obtained from patients in Canadian hospitals as part of the Canadian Ward Surveillance Study (CANWARD) and to determine how often the mcr-1 gene is detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 31 publications
2
15
3
Order By: Relevance
“…Further research is needed with larger cohorts from different geographic locations, representative populations, and demographics to fully understand the prevalence of mcr-1 in our local context. The 21 mcr-1 positive strains detected in this study had MICs of only 4-8 mg/L, which was lower than that of previously reported mcr-carrying Enterobacteriaceae bacteria (MICs of 4-16 mg/L), which showed moderate level of colistin resistance [17]. These results indicate that the resistance level of colistin in E. coli from children was different from that of adults.…”
Section: Discussioncontrasting
confidence: 80%
“…Further research is needed with larger cohorts from different geographic locations, representative populations, and demographics to fully understand the prevalence of mcr-1 in our local context. The 21 mcr-1 positive strains detected in this study had MICs of only 4-8 mg/L, which was lower than that of previously reported mcr-carrying Enterobacteriaceae bacteria (MICs of 4-16 mg/L), which showed moderate level of colistin resistance [17]. These results indicate that the resistance level of colistin in E. coli from children was different from that of adults.…”
Section: Discussioncontrasting
confidence: 80%
“…Thirteen colistin-resistant clinical isolates were tested (Table 4), including P. aeruginosa, A. baumannii, K. pneumoniae, E. coli, and E. cloacae. Notably, the two E. coli isolates in the panel were known to harbor the mcr-1 gene plasmid that transcribe phosphoethanolamine transferase to confer colistin resistance (18). According to the Clinical and Laboratory Standards Institute (CLSI) (28), an MIC of Յ2 g/ml against P. aeruginosa and A. baumannii denotes susceptibility to colistin, while no breakpoint is currently established against Enterobacteriaceae.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial strains from CANWARD were clinical specimens collected from patients suffering from a presumed infectious diseases admitted in a participating medical center across Canada. The two colistin-resistant E. coli strains from the CANWARD study had been reported to harbor the plasmid-mediated colistin resistance gene mcr-1, but not mcr-2 (18). The efflux-deficient P. aeruginosa strains PAO200 and PAO750 were obtained from previous studies (41,42).…”
Section: Methodsmentioning
confidence: 99%
“…All isolates were sequence type ST3521, and varied between 1 and 4 SNVs with 98.7% of the core genome analysed. The E. coli geese cluster differed by >12,000 SNVs when compared to nine colistin‐resistant E. coli isolates identified in humans from hospitals identified in the CANWARD study between 2007 and 2016 (Walkty et al, ).…”
Section: Resultsmentioning
confidence: 99%